Efektifitas Penerapan Pendidikan Karakter Pada Kurikulum 2013 Pembelajaran Tematik Di Sekolah Dasar Inpres 6/75 Ta' Tanete Riettang Kabupaten Bone - Abd Hafid; rosmalah rosmalah; sultan sultan (Universitas Negeri Makassar, 2019)
The effectiveness of the implementation of 2013 curriculum character education still needs to be assessed. The focus of the problem: What is the plan for implementing character education in thematic learning of 2013 curriculum at Primary School Inpres 6/75 Ta 'Tanete Riattang, Bone Regency and how effective is the implementation of character education in 2013 thematic learning curriculum at Primary School Inpres 6/75 Ta' Tanete Riattang, Bone Regency?. The purpose of this study was to describe the implementation plan of character education in thematic learning at Primary School Inpres 6/75 Ta 'Tanete Riattang, Bone Regency and describe the effectiveness of the implementation of character education in 2013 curriculum thematic learning at Primary School Inpres 6/75 Ta' Tanete Riattang District Bone. The research approach was qualitative and the type of research was descriptive research. This research was conducted in Primary School Inpres 6/75 Ta’. Data sources in this study were teachers and students in grades I, II, IV, and V. Data collection techniques in this study were documentation and observation sheets. Data analysis techniques used were data reduction, data presentation, and drawing conclusions. The results showed that the planned implementation of character education in the thematic learning of 2013 curriculum and the implementation of character education in the thematic learning of 2013 curriculum at Primary School Inpres 6/75 Ta'were categorized very good. The study concluded that the planning and implementation of character education in 2013 curriculum thematic learning at Primary School Inpres 6/75 Ta’ were effective.